Relationship between histopathological features of aspirated thrombi and long-term left ventricular function in patients with ST-segment elevation myocardial infarction - Mehmet Onur Omaygenç; Cem Doğan; Adnan Somay; Oğuz Karaca; Ruken Bengi Bakal; Mehmet Kamil Teber; Suzan Hatipoğlu; Zübeyde Bayram; Cihangir Kaymaz; Nihal Özdemir (KARE Publishing, 2020)
Objective: This study was an investigation of the severity of inflammation (SOI) in aspirated material and thrombus age to examine any association with pre-discharge and long-term left ventricular (LV) function after ST-elevation myocardial infarction (STEMI). Methods: The study group comprised 25 patients with STEMI from whom an occlusive thrombus was aspirated from the infarct-related artery with a 7-F catheter. The SOI in the aspirate was determined according to the mean leukocyte count in 5 high-power magnification fields and graded as mild in the presence of ≤100 leukocytes per field or significant if there were >100 leukocytes per field. The thrombi were categorized as fresh or lytic/organized (L/O) using predefined criteria. Echocardiographic assessment was performed prior to discharge and at 1 year. Adverse left ventricular remodeling (LVR) was defined as a 20% increase in LV end-diastolic volume in comparison with baseline values. Results: LVR was observed in 8 patients. The mean leukocyte count of the aspirate (127.5+-86.0 vs 227.2+-120.7; p=0.026) and frequency of significant inflammation (35% vs 75%; p=0.046) were significantly higher in the group with LVR. The serum high-sensitivity C-reactive protein (hsCRP) level was significantly correlated with the leukocyte count of the aspirate (r=0.532; p=0.006). An L/O thrombus was related to better pre-discharge and long-term LV volumes and ejection fraction values compared with a fresh thrombus. Conclusion: A significant increase in the leukocyte count in the aspirate and a fresh thrombus might predict long-term LV functional deterioration irrespective of the clinical and procedure-related characteristics. In addition, serum markers of inflammation, like hsCRP, might also reflect the intensity of the local inflammatory response at the site of occlusion.